Association between time-related work factors and dietary behaviors: results from the Japan Environment and Children's Study (JECS) - Rie Tanaka; Mayumi Tsuji; Koichi Kusuhara; Toshihiro Kawamoto; Japan Environment and Children's Study Group (Komiyama Printing Co. Ltd, 2018)
Abstract Background Few studies have examined the association of workhours and shift work (referred to here as "time-related work factors") with dietary behaviors. We aimed to investigate this association, as well as the dietary behaviors among individuals with occupations characterized by time-related work factors. Methods A cross-sectional study was performed using data from the Japan Environment and Children's Study. The study included 39,315 working men. Dietary behaviors (i.e., skipping breakfast, eating out, eating instant food, overeating, and eating fast) were assessed with a self-reported information from the Food Frequency Questionnaire. Logistic regression analysis was conducted to examine the associations of time-related work factors with dietary behaviors and dietary behavior tendencies among those in occupations characterized by long workhours and/or shift work. Results Long workhours were associated with high frequencies of skipping breakfast, eating out, eating instant food, overeating, and eating fast. The frequency of having shift work was associated with high frequencies of skipping breakfast, eating out, and eating instant food. Several occupations involving long workhours and/or shift work showed specific dietary behaviors; in some occupations, the level of significance changed after adjusting for time-related work factors in addition to other potential confounding factors. Conclusions Time-related work factors may help explain workers' dietary behaviors. Long workhours and shift work may lead to poor dietary behaviors. Other factors influenced by occupation itself, such as food environment, may also influence workers' dietary behaviors. Workhours and/or shift work, and these other work factors, should be given attention in workplace health promotion.